Investigation of an ammonium carbamate–based SCR system for NOx reduction in diesel engines under transient conditions. (15th July 2022) - Raza, Hassan; Woo, Sanghee; Kim, Hongsuk
Abstract: The deNOx performance of a selective catalytic reduction (SCR) system using ammonium carbamate (AC) was investigated and compared with that of a urea water solution (UWS). The effects of the NH3 /NOx (α) ratio, injection threshold temperature (Tinj ), and a zero-dimensional ammonia adsorption-desorption model on NOx conversion efficiency were evaluated. World harmonized transient cycle (WHTC) and non-road transient cycle (NRTC) tests were conducted using a 3.9-L diesel engine over a Cu-zeolite catalyst. The NOx conversion efficiency of AC in the WHTC and NRTC was increased compared with that of UWS during the cold phase by 6.43% and 8.71%, respectively, and during the hot phase by 14.79% and 11.93%, respectively. Gaseous ammonia injection at a low Tinj can explain improved deNOx performance, as increasing Tinj leads to a decrease in NOx conversion efficiency. Increasing the α ratio effectively increases NOx conversion efficiency, but a high α ratio leads to ammonia slip. Ammonia injection using a model-based control increased cold-start deNOx performance. These promising results provide an alternative pathway to controlling NOx emissions from heavy-duty diesel engines. Highlights: Ammonium carbamate-based SCR system is investigated for NOx reduction. DeNOx performance of ammonium carbamate is better than urea water solution. Decreasing injection threshold temperature (Tinj ) increases the deNOx performance. Model-based control of ammonia increases cold-start deNOx performance.